Foam fractionation removal of multiple per‐ and polyfluoroalkyl substances from landfill leachate. Issue 5 (12th September 2021) - McCleaf, Philip; Kjellgren, Ylva; Ahrens, Lutz
Abstract: Per‐ and polyfluoroalkyl substances (PFAS) are a common contaminant in municipal landfill leachate and are recognized as a pollutant on global scale. The present work examined foam fractionation (FF) in batch and continuous modes as an appropriate treatment technique for PFAS removal for the landfill leachate and found stable removal efficiency of greater than 90% for PFOA (C7 ), PFOS (C8 ), PFHxS (C6 ), and PFHpA (C6 ) and 6:2 FTSA (C6 ). For other PFAS such as PFNA (C8 ), PFPeS (C4 ), PFHxA (C5 ), PFHpS (C7 ), and PFBS (C4 ), a less stable removal between 80% and 50% was achieved while between 50% and 20% removal was observed for EtFOSAA (C8 ), PFBA (C3 ), PFDA (C9 ), FOSA (C8 ), PFPeA (C4 ), and MeFOSAA (C8 ). Increased air flowrate, addition of iron (III) oxide (Fe +3 ) coagulant, conductivity, and greater untreated leachate PFAS concentration were factors resulting in increased removal efficiency for the majority of PFAS. Article Impact Statement: Efficient PFAS removal from landfill leachate using surface‐active foam fractionation treatment with examination of key process parameters.